Test plivanja i ehokardiografski rezultati kod juniora - igraca vaterpola - Petridis, L.; Kubatova, J.; Petridou, K. (Facta Universitatis: Series Physical Education and Sport, 2003)
The purpose of this study was to evaluate the results of a swim-test which we repeatedly used for the assessment of the fitness level in Hungarian male junior water-polo players by relating the results to the players' echocardiographic parameters. It could be a point of interest if a relationship between the results of the swim-test and cardiac function were established. 26 male junior elite and 11 Olympic champion water-polo players participated in the swim-tests and the echocardiographic measurements. 25 healthy men served as a non-athletic comparison group. The swim test included the time result of a 30 m maximal intensity swim (Tmax), the mean time of a 6×30 m interval swim (Tmean), the number of heart beats during the 4 minutes of recovery (P4) and the difference between the heart beats during the first and the second half min. of recovery (Delta). Morphological and functional parameters of the heart were measured by echocardiography. The observed variables were related to body size by indices in which the exponents of the numerator and the denominator were matched. The echocardiographic measurements showed clear signs of left ventricular hypertrophy in the water-polo players compared to the non-athletic group. Between the swim-test and the echocardiographic measurements no close correlations were found, though when we correlated the cardiac parameters with swimming velocity (instead of the time results of the swim-test) some correlations became stronger. The results suggest that there was no linear relationship between the swim-test and the cardiac parameters; however, a parallel adaptive improvement of the junior players to non-athletes could be noticed in both measurements as a result of regular training. It appears justifiable that associations should be sought above all in the pace of the respective improvements on a proportional basis. The current swim-test seems to be not precise enough to evaluate the cardiac function of the athletes. The methodological conception in relating a resting parameter (echocardiographic measurements) to maximal dynamic ones (swim-test) needs further investigation.